Diseño e implementación de un sistema de control de temperatura con un interfaz de pantalla tactil. - Pichucho Tocto, Edwin Javier (2009)
This project designed and implemented a system of temperature control with a touchscreen interface / temperature controller. In addition it will be possible to control monitor and record the temperature of the process. The RS 485 communication between the HMI 601 or 605 and the controller is done BrainChild brand P41 temperature, with Studio HMI software, software Studio HMI programming master and slave port numbers configured etc. communication. Besides the design and programming of each screen is done for the To make a friendly interface for the operator, for example screen History, Join Set Point and times, temperature ranges, etc..